Activation of the beta-globin locus control region precedes commitment to the erythroid lineage. - Jiménez, G (1992)
The beta-globin locus control region (LCR) is characterized by erythroid-specific DNase I hypersensitive sites and is involved in the chromatin organization, transcriptional potentiation, developmental regulation, and replication timing of the entire beta-globin gene cluster. When and how the LCR is first activated during erythropoiesis is not known. Here we analyze the chromatin structure of the LCR during early hematopoietic differentiation using nontransformed, multipotential, growth factor-dependent, murine hematopoietic progenitor cells. We show that LCR hypersensitive sites characteristic of erythroid cells are present in three independent multilineage progenitors [FDCP (factor-dependent cell, Paterson)-mix A4, B6SUtA, and LyD9] under conditions of self-renewal. Induction of differentiation down a nonerythroid pathway causes a progressive loss of hypersensitivity in the LCR. These results show that the beta-globin LCR is in an active chromatin configuration prior to erythroid commitment and indicate a significant role for selective gene repression in lineage specification.